Using task-based learning approach to foster oral production in 8° graders. - Fuelantala Pulido, Dayana Catalina; González Mesa, Pedro Alejandro; Asesor (Corporación Universitaria Minuto de Dios, 2016)
This research project is focused on the description and analysis of the processes of fostering oral abilities with the implementation of Task Based Learning using speaking techniques in interactive method with a story as a tool in eight graders students in a public school in Bogota. Thirteen students participated in the project for more than two months. Among the main sources to obtain data, questionnaires, researcher observations, students’ portfolios and students recording transcription were used. Through the data analysis it was revealed that students during this pedagogical implementation faced different aspects to improve their English level in class; to do it were used strategies and three techniques implemented in relation with activities such as: minimal responses, talk about English, picture activity-game, guessing activity-game and story activity-game.
Keywords: Analysis of the Processes; Activity-Game; Speak in English; IDIOMAS EXTRANJEROS; APRENDIZAJE; LENGUAJE Y LENGUAS; INGLES